2019
DOI: 10.3847/2041-8213/ab2ba2
|View full text |Cite
|
Sign up to set email alerts
|

A Gap in the Mass Distribution for Warm Neptune and Terrestrial Planets

Abstract: Structure in the planet distribution provides an insight into the processes that shape the formation and evolution of planets. The Kepler mission has led to an abundance of statistical discoveries in regards to planetary radius, but the number of observed planets with measured masses is much smaller. By incorporating results from recent mass determination programs, we have discovered a new gap emerging in the planet population for sub-Neptune mass planets with orbital periods less than 20 days. The gap follows… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Atmospheric erosion by high-energy stellar radiation (also known as A&A 636, A89 (2020) photoevaporation) is believed to play a major role in shaping both the Neptunian desert and the bimodal distribution of planetary radii. Moreover, Armstrong et al (2019) found a gap in the mass distribution of planets with a mass lower than ∼20 M ⊕ and periods shorter than 20 days, so far without any apparent physical explanation.…”
Section: Introductionmentioning
confidence: 99%
“…Atmospheric erosion by high-energy stellar radiation (also known as A&A 636, A89 (2020) photoevaporation) is believed to play a major role in shaping both the Neptunian desert and the bimodal distribution of planetary radii. Moreover, Armstrong et al (2019) found a gap in the mass distribution of planets with a mass lower than ∼20 M ⊕ and periods shorter than 20 days, so far without any apparent physical explanation.…”
Section: Introductionmentioning
confidence: 99%
“…One can expect that terrestrial planets that formed close to their star, or in case of Mercury to the Sun, might have accreted significantly volatile depleted material after the gas disk dissipated and during the so-called giant impact phase. Lower mass planets that formed further out and migrated inward to close-orbital distances would have lost their primordial H 2 -He-dominated atmospheres due to EUV-driven hydrodynamic escape (Owen and Wu 2017;van Eylen et al 2018;Armstrong et al 2019). That there is a sub-Neptune-desert or a photoevaporation valley in close-orbital distances is also confirmed by exoplanet observations with the Kepler space telescope (McDonald et al 2019).…”
Section: Introductionmentioning
confidence: 76%
“…TOI-125b, TOI-125c and TOI-125d are thus all mini-Neptunes with similar radii, but different masses yielding a high-low-higher density pattern outwards in the system. The planets straddle the gap identified in the mass-period plane by Armstrong et al (2019). All three planets have the same orbital inclination to within a degree.…”
Section: Joint Modelling With Exofastv2mentioning
confidence: 85%